Holistic e-learning in Nigerian Higher Education Institutions - Oye, N. D. (Journal of Computing, 2010)
This paper discusses holistic e-learning in Nigeria higher Education (HE) institutions. We assume, however that, a semblance of e-learning exist, at the departmental levels of the HE institutions, rather than the whole institutions. A case study of e-learning technology tools at Federal University of Technology Yola (FUTY) shows that ICT infrastructure is more tilted to the management (offices) and schools/faculty (offices) than the departments, lecture halls and students hostels. This paper is looking into the disparity observed between the successful adoption of technology for administrative purpose and the less successful adoption of technology with regards to teaching and learning. That is the major reasons why we have partial e-learning in most Nigerian HE institutions. The paper is proposing a move from separate e-learning research focus to holistic research focus, by adopting social software as a new approach for networking within the institutions and with other institutions. Finally the expected benefits of holistic e-learning were enumerated.